The Impact of Zhihar on Women’s Rights in the Perspective of Gender Jurisprudence - Lina Nur Anisa (The Indonesian Journal of Islamic Law and Civil Law, 2024)
This article discusses the issue of zhihar in the context of gender jurisprudence, which often leads to injustices for women within Islamic marriage law. With the growing awareness of gender justice, this research aims to explore the impact of zhihar on women's rights and assess the need for legal reinterpretation to create fairer solutions. The research method employed is a literature analysis, examining various references from accredited books and journals, along with a qualitative approach to understand the perspectives of classical and contemporary scholars. The findings reveal that zhihar, as a legal practice, frequently places women in a disadvantaged position regarding both sanctions and the protection of rights. Additionally, a gender jurisprudence approach can provide new insights for reconstructing this law, offering fairer solutions for both parties. This article recommends more inclusive reforms to Islamic family law and emphasizes the role of scholars in advocating for gender justice as a crucial step toward a more equitable legal system for women.